Correlation between fine particulate matter air pollution and under-five children mortality in Indonesia: A secondary data analysis of WHO Global Health Observatory - Soleman, Sani; Rifai, Muchamad; Indah, Meiyla Farikha (YCAB Publisher & IAKMI SULTRA, 2023)
Background: Fine particulate matter (PM2.5) is an environmental factor contributing to the death rate. However, few studies have demonstrated the association between PM2.5 and the under-five mortality rate. Objective: To determine the correlation between PM2.5 and under-five children mortality in Indonesia. Methods: A secondary data analysis of the WHO Global Health Observatory on Environmental Pollution and Children Mortality during 2012-2016 was conducted. The environmental pollution was measured by PM2.5 levels (μg/m3) in rural, urban, and both areas. Mortality data were categorized by specific causes—meningitis/encephalitis, acute lower respiratory infection, diarrhoeal diseases, tetanus, prematurity, birth asphyxia, and congenital anomalies. Data were analyzed using Mann-Whitney and Spearman correlations. Results: The PM2.5 total concentration in urban areas was greater than in rural areas for four years (18.4±1.19 vs. 15.4±1.1, p = 0.016). Prematurity, acute lower respiratory infection, and birth asphyxia were the leading causes of under-five mortality. The PM2.5concentration in urban and rural areas was significantly associated with an acute lower respiratory infection, tetanus, prematurity, birth asphyxia, and congenital anomalies (p <0.05). Additionally, the PM2.5 concentration was negatively correlated with tetanus, prematurity, birth asphyxia, and congenital anomalies (p <0.001; r = -0.8, -0.8, -0.82, -0.83, respectively). Conclusion: PM2.5 air pollution was correlated with tetanus, prematurity, birth asphyxia, and congenital anomalies from 2012-2016 in Indonesia. Further action is needed to handle the sources of air pollution contamination to preventing under-five mortality in the community.